Temporal and spatial changes of total concentrations of «carbon, nitrogen, phosphorus» in several locations of Al Kabeer Al Shamali River - كبيبو, عيسى; عباس , جميل; محمود , اونج (Latakia University Journal -Biological Sciences Series, 2021)
The catchment of the Al Kabeer Al Shamali River has been a place of intensive economic transformation since the 1985. The purpose of this study is to determine the water quality of the 16 Tishreen Dam Lake to find out the possibility of diverting part of the lake water to the drinking water network in Lattakia city. Water samples were taken seasonally for analysis to determine the suitability for drinking from three sites, namely the northern inlet to the lake (Ghamam Bridge), the 16 Tishreen Dam Lake, and the Ain al-Bayda irrigation tunnel during the period from August 2018 to November 2019. The results showed significant differences at 0.05 level for NPOC concentrations in the study area. The means of carbon concentrations were as follows (2.84 mg L-1) in Ghamam Bridge water, then increased to (3.24 mg L-1) in the water of dam lake, then decreased to (2.70 mg L-1) in the tunnel. The NPOC increase in the lake water was attributed to a large scale retention of export NPOC from river. This result promoted us to study the carbon, nitrogen, and phosphor stoichiometry of the studied sites water. The results showed that the means of ratios «NPOC: TN, NPOC: TP and TN: TP» in the river water were 6, 54,10 respectively, then increased to 15, 284, 19 in the dam water, then decreased in the tunnel water to 9, 69, 11. These results showed that dam lake water was generally richer in organic carbon relative to dam inlet and dam outlet. On the other hand, the N: P ratio gave the same trend as for C: N ratio that indicates for eutrophication state.